Small and medium size companies competiveness in Croatian regional framework - Zlatan Fröhlich (European Regional Science Association (ERSA), 2013)
Small and medium enterprises (SMEs) represent an important part of the Croatian economy. In 2011 SMEs achieved a share of 50.2% of gross domestic product (GDP), 65.5% of employment and 42% of Croatian exports. In the paper will be elaborated importance of the small and medium enterprise sector in Croatia as well as presented institutional and legislative framework for the small and medium enterprise sector in Croatia and describe distribution of competences for making policy decisions related to small and medium enterprises, implementation of those decisions at the level of state institutions, and the availability of support for the small and medium enterprise sector. The sources of financial support for the development of small and medium enterprises in Croatia and the access and availability of information and advisory services, as one of the preconditions for development of entrepreneurship will be explained. Approach to the analysis of regional policy in Croatia is to concentrate upon three main fields. These are: 1. assessment of the overall policy framework for regional development, including the current legal framework in particular policies, legal acts and regulations, 2. assessment of the institutional and administrative capacity in place, 3. appraisal of the types of regional development instruments currently deployed and their effectiveness in dealing with development needs at national, regional and local level. Paper will concentrate on small and medium size companies competiveness in regional framework. Data on employment includes aggregate data on the number of employees in crafts businesses and small and medium enterprises. All the other analyses are focused exclusively on the small and medium enterprise sector, excluding crafts businesses, while micro enterprises are included in the small enterprise category. The national development strategy sets the context for balanced regional development both at national and sub-national level as well as draws attention to development needs of the ?assisted areas? as well as counties highlighting their different development profiles. It brings together the main analytical parts: policy framework, institutional context and finally an assessment of the existing development interventions on county, NUTS 2 and assisted areas level. Paper will deal with economic performance of SME?s on regional level and indicate the role of national and regional supporting measures in development of that sector. Key words: SME?s competiveness on regional level, O43 - Institutions and Growth, R11 - Regional Economic Activity: Growth, Development, Environmental Issues, and Changes, R12 - Size and Spatial Distributions of Regional Economic Activity
Keywords: O43; R11; R12; 330; SME?s competiveness on regional level; Institutions and Growth; Regional Economic Activity: Growth; Development; Environmental Issues; and Changes; Size and Spatial Distributions of Regional Economic Activity